The Socio-administrative Study of Indigenous People in the Implementation of Education Policy in Merauke Regency - Fenanlampir, Casimirus Andy (KnE Social Sciences, 2025)
This research, using a socio-administrative approach, aims to provide an in-depth description of the knowledge and understanding of the dimensions of indigenous people in the implementation of public policies in the field of education in Merauke Regency. It uses a case study method with qualitative research design. The study shows that the involvement of indigenous communities, particularly the Marind people, is crucial in the implementation of public education policies. Cultural values, socio-economic conditions, and regional topography are key factors that influence the success of these policies and must be considered in both policy formulation and execution. In addition, the existent factor of the indigenous institution as a representative of the Marind community is also important to consider and involve in every policy determination, even though legally formal duties, responsibilities, and authorities of the customary council have not been accommodated, either in the form of regional regulations, regent regulations, or in the form of village regulations. This study concludes that the success of implementing public policy in the field of education in Merauke Regency is largely determined by the involvement of the Marind indigenous people. The Marind indigenous people as subjects and objects of policy implementation are important to note. The unique priorities of indigenous communities for governance are important when considering the issues they experience.